IN THE GLOBAL ECONOMY OF MOBILE COMMUNICATION NETWORKS (Marketing Journal, 2025)
Mobile networks in the 21st century have become an integral part of the global economy. Their development and progress have a significant impact on the economic and social systems of all countries worldwide. Mobile networks have modernized communication sy stems between people, simplified economic activities, and created new opportunities for business and trade. Mobile networks are developed at different levels in various countries. In developed countries such as the USA, European countries, and Japan, mobile networks are widely spread and contribute to economic growth through innovations. In developing countries, mobile networks play an important role in providing access to information and creating new approaches in education and healthcare. Mobile networks facilitate the globalization of business and trade, the development of e -commerce, especially online trading and financial services, which make a significant contribution to economic growth. Moreover, mobile networks help create jobs and im prove economic competitiveness through transfers and business services. This provides an analysis of the role of mobile networks in the global economy and their development levels.
Keywords: mobile networks; global economy; innovations; mobile financial services; mobile infrastructure; mobile competition